Greater Cairo : A Proposed Urban Transport Strategy - World Bank (Washington, DC, 2013)
The objective of the urban transport strategy note (UTSN) is to provide an assessment of the urban transport system in Greater Cairo (GC), identify what now appear to be the most pressing urban transport problems, and framework for urgent policy actions and investment priorities that would be the basis of a formal transport strategy to be adopted and implemented by the authorities of the metropolitan area of Cairo. This note is essentially based on a thorough review of the 2002 Urban Transportation Master Plan for GC and a rapid analysis of the current conditions and performance of the urban transport system. This note includes nine chapters. The first chapter provides a quick overview of the current situation of the UT in GC. In chapter two, present the main guiding principles and key components of the proposed strategy to prepare the ground for the following chapters. Chapter three to nine elaborate on the issues and policy recommendations for each of the components of the strategy: organization and operation of public transport systems (chapter three), investment policy in urban transport (chapter four), traffic management policy (chapter five), introducing travel demand management (chapter six), strengthening traffic enforcement (chapter seven), building urban transport institutions (chapter eight), affordability of urban transport services and financing policy (chapter nine). Finally a last chapter (ten) presents a priority action program including selected coherent mix of policy actions and cost effective investments to be implemented in the short and medium terms to initiate a process of long term improvements of the UT conditions and operations in Cairo metropolitan.